Wischnewski Spots and Black Oesophagus in Suspected Fatal Hypothermia in a Brown Howler Monkey (Alouatta guariba clamitans) and a Rabbit (Oryctolagus cuniculus). (July 2021) - Almeida, Bruno A.; Santos, Igor R.; Henker, Luan C.; Lorenzett, Marina P.; Ferrari, Flávia E.; Surita, Lívia E.; Panziera, Welden; Pavarini, Saulo P.; Driemeier, David
Summary: Fatal hypothermia represents a diagnostic challenge in veterinary pathology. Wischnewski spots (WS) and black oesophagus (BO) have been described in human cases of fatal hypothermia but rarely in animals. We now describe WS and BO in suspected fatal hypothermia in a free-ranging brown howler monkey ( Alouatta guariba clamitans ) and a pet rabbit ( Oryctolagus cuniculus ). Both animals had dark spots resembling WS on the gastric mucosa and the monkey also had BO with haematin deposition. In both cases, stress factors and relatively cold environmental conditions were present prior to death.